Efforts to Improve Access to Primary Healthcare Services in Archipelagic Regions : A Literature Review - Ruth Christy Setyaningtyas; Dumilah Ayuningtyas (Indonesian Journal of Global Health Research, 2025)
Healthcare delivery in archipelagic regions faces significant challenges, including limited access, inadequate infrastructure, and a shortage of healthcare professionals. Achieving universal health coverage in these regions requires innovative strategies and approaches. This study aims to identify regulations, challenges, and provide recommendations to improve access to healthcare services in archipelagic regions. A literature review method was employed, utilizing two databases, Google Scholar and ScienceDirect. Keywords used include “Pelayanan Kesehatan di Kepulauan” OR “archipelago healthcare” OR “health services in islands”. From 515 articles with publications from 2019 – 2024 initially retrieved, only seven were analyzed after screening using the PRISMA diagram based on predetermined criteria. The findings reveal that common challenges across archipelagic regions include geographical conditions, infrastructure limitations, and shortages in healthcare workforce quantity. Innovative efforts, such as telemedicine, hospital ships, health boats, and village health posts, have been implemented in several countries with similar geographical characteristics and proven effective in overcoming these access barriers. In conclusion, despite the complex challenges in archipelagic regions, existing regulations and various implemented efforts have improved healthcare access, fulfilling community health needs. These initiatives contribute to accelerating the equitable delivery of sustainable and high-quality healthcare services.